Neuroregenerative effects of Centella asiatica (L) urban on in vitro and in vivo oxidative stress-induced models of neurodegenerative disease - Mansor, Nur 'Izzati (2021)
Oxidative stress and reactive oxygen species (ROS) have been closely linked to the development of neurodegenerative diseases (ND). Neuroregenerative is the ability of therapeutic agent to repair and restore the normal function of degenerated neurons. Centella asiatica (CA) (L.) Urban is well-known for its nutritional benefits. Its phytochemicals have been documented to have neuroprotective, neuroregenerative and antioxidant effects besides being traditionally known for its raw consumption to enhance learning and memory. The present study aims to investigate the neuroregenerative effects of the Standardized raw extract of CA (RECA) in in vitro and in vivo oxidative stress-induced ND models. For the in vitro model, hydrogen peroxide (H2O2)-induced oxidative stress and apoptotic death in neural cells derived from transgenic mouse embryonic stem cell line (46C) and rat amniotic fluid (R3) stem cell lines were used. Pre-treatment with H2O2 for 24 h, in a dose-dependent manner, damaged the neural cells as marked by decrease in the cell viability, significant increase in the intracellular ROS accumulation and increase in apoptotic rate as compared to the untreated cells. Treatment with RECA for 48 h was observed to restore cell survival and promote neurite outgrowth in the H2O2-damaged neurons by increasing cell viability and decreasing the ROS activity of 46C- and R3-derived neural cells. RT-qPCR analysis revealed that RECA upregulated the level of antioxidant genes such as theoredoxin-1 (Trx1) and heme oxygenase-1 (HO1) of treated cells, as well as the mRNA levels of neuronal-specific markers such as Tuj1 and MAP2, suggesting their contribution in neuritogenic effect. For the in vivo ND model, 2 vessels occlusion via permanent bilateral occlusion of common carotid arteries (PBOCCA) surgery method has been employed to develop chronic cerebral hypoperfusion (CCH) model in rats. In the first part of the in vivo study, the effect of acute and chronic oral treatment of RECA at 300 mg/kg on oxidative stress were assessed in the hippocampus of rats. An increase in malondialdehyde (MDA) level of PBOCCA rats was inhibited by chronic treatment of RECA, along with the increase in reduced glutathione (GSH) level. Acute and chronic oral treatments of RECA promote the upregulation of superoxide dismutase (SOD1) and HO1 gene expression in the hippocampus of PBOCCA rats. However, the expression of Trx1, GFAP and TGF-β1 genes were remained unchanged. These results lead to the second part of the study where acute and chronic oral treatment of RECA were assessed for their learning and memory functions, as well as the underlying mechanism in attenuating neuronal loss. Acute and chronic oral treatment of RECA at 300 mg/kg were unable to restore spatial learning and reference memory impairments in PBOCCA rats. Acute treatment of RECA also did not exert any effect on hippocampal long-term potentiation. RT-qPCR analysis revealed that RECA upregulated the expression of Tuj1, NeuN, BDNF and CamkII genes, signifying the neuroregenerative potentials of RECA. However, chronic treatment of RECA did not exert any effect on MAP2, SYP, ChAT and AChE genes in the hippocampus of PBOCCA rats. These findings therefore implicate the potential of RECA in inhibiting neurodegeneration by ameliorating oxidative damage and promoting neuronal regeneration.